2002
DOI: 10.1161/01.str.0000033932.34467.97
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Disruption and Matrix Metalloproteinase-9 Expression During Reperfusion Injury

Abstract: Background and Purpose-Most experimental models of cerebral ischemia use mechanical methods of occlusion and reperfusion. However, differences between mechanical reperfusion versus clot thrombolysis may influence reperfusion injury profiles. In this study we compared blood flow recovery, blood-brain barrier (BBB) permeability, and matrix metalloproteinase-9 (MMP-9) expression in cortex after mechanical versus thrombolytic reperfusion in rat focal ischemia. Methods-Male spontaneously hypertensive rats were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
2
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(155 citation statements)
references
References 34 publications
3
148
2
2
Order By: Relevance
“…Consistent with these data, the expression and activity of MMP-2 was greater than that of MMP-9 in wildtype mice. MMP-2 is considered a constitutively expressed MMP, whereas MMP-9 is expressed at low levels under normal conditions (Gottschall et al, 1995;Yong et al, 1998;Planas et al, 2001) but is induced under pathological conditions, such as cerebral ischemia and neurodegeneration (Aoki et al, 2002;Lo et al, 2002;Lee et al, 2003). It is possible that under pathological conditions, MMP-9 may play a greater role in A␤ clearance; its expression is certainly increased in astrocytes surrounding amyloid plaques in aged APPsw mice.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these data, the expression and activity of MMP-2 was greater than that of MMP-9 in wildtype mice. MMP-2 is considered a constitutively expressed MMP, whereas MMP-9 is expressed at low levels under normal conditions (Gottschall et al, 1995;Yong et al, 1998;Planas et al, 2001) but is induced under pathological conditions, such as cerebral ischemia and neurodegeneration (Aoki et al, 2002;Lo et al, 2002;Lee et al, 2003). It is possible that under pathological conditions, MMP-9 may play a greater role in A␤ clearance; its expression is certainly increased in astrocytes surrounding amyloid plaques in aged APPsw mice.…”
Section: Discussionmentioning
confidence: 99%
“…30 tPA has no effect on the integrity of the BBB in physiological conditions either in vitro or in vivo. Some authors 34 but not all 18 suggest that tPA amplifies ischemia-induced BBB breakdown. Interestingly, the studies that showed an effect of tPA on BBB were performed on hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the studies that showed an effect of tPA on BBB were performed on hypertensive rats. 34 In a recent report, Yepes and colleagues 15 showed that tPA can lead to an opening of the BBB by a mechanism that involves LRP. This discrepancy with the present results could be explained by the fact that here, tPA was injected intravenously, as it is usually performed in humans, whereas it was injected directly into the CSF in the study published by Yepes and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…15 In rat embolic stroke models, clot lysis with tPA increases ischemic brain MMP-9 levels, and co-treatment with MMP inhibitors reduced tPAinduced hemorrhagic transformation and brain injury. 16,17 The "tPA-induced MMP-9" hypothesis is further supported by a study showing that after focal cerebral ischemia, MMP-9 levels are lower in tPA knockout mice compared with wild-type mice. 18 But how does tPA amplify MMP-9?…”
Section: Tpa and Matrix Metalloproteinasesmentioning
confidence: 93%